2003
DOI: 10.1021/ol034943n
|View full text |Cite
|
Sign up to set email alerts
|

New Air-Stable Planar Chiral Ferrocenyl Monophosphine Ligands:  Suzuki Cross-Coupling of Aryl Chlorides and Bromides

Abstract: [reaction: see text] A novel class of planar chiral electron-rich monophosphine ligands has been developed. The modular design allows a short and efficient synthesis of an array of aryl-ferrocenyl derivatives carrying the donating bis(dicyclohexyl)phosphino moiety. These new ligands have successfully been applied in the palladium-catalyzed Suzuki cross-coupling of activated as well as nonactivated aryl chlorides at room temperature. The asymmetric coupling of an aryl bromide and an aryl boronic acid was also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(85 citation statements)
references
References 22 publications
4
76
0
5
Order By: Relevance
“…[196,197] In der Gruppe von Johannsen wurden die luftstabilen Ferrocenylmonophosphane ( P R)-186 als chirale Liganden für die Palladium-katalysierte Synthese von (M)-179 [198] aus 175 und 183 nutzbar gemacht (Schema 39). [199] In Abhängigkeit von den Arylsubstituenten an ( P R)-186 wurden Enantiomerenüberschüsse zwischen 43 und 54 % ee erhalten.…”
Section: Schema 36 Elektrochemische Oxidative Homokupplung Von 2-napunclassified
“…[196,197] In der Gruppe von Johannsen wurden die luftstabilen Ferrocenylmonophosphane ( P R)-186 als chirale Liganden für die Palladium-katalysierte Synthese von (M)-179 [198] aus 175 und 183 nutzbar gemacht (Schema 39). [199] In Abhängigkeit von den Arylsubstituenten an ( P R)-186 wurden Enantiomerenüberschüsse zwischen 43 und 54 % ee erhalten.…”
Section: Schema 36 Elektrochemische Oxidative Homokupplung Von 2-napunclassified
“…In 2003, Johannsen and Jensen communicated the asymmetric synthesis of 2,2'-dimethyl-1,1'-binaphthalene by using 2-methylnaphthalen-1-ylboronic acid and a planar chiral bis(dicyclohexyl)-phosphinoferrocene/palladium complex as catalyst, in 65 % yield but with only 54 % enantiomeric excess. [12] Although other related successful couplings of less hindered fragments have been reported by Yin and Buchwald (aryl-naphthyl enantioselective heterocoupling), [13] Colobert and co-workers (asymmetric synthesis of 2,2'-dimethoxy-1,1'-binaphthalene), [14] and Mikami et …”
Section: Introductionmentioning
confidence: 99%
“…This was first illustrated in the total synthesis of Vancomycin [7] by Nicolaou, who obtained a chiral biaryl with up to 55% diastereomeric excess in the presence of a chiral ligand. Enantioselective Suzuki couplings induced by a chiral ligand have also been reported by Cammidge, [8] Buchwald, [9] Baudoin, [10] Johannsen, [11] and, very recently, by Mikami. [12] We recently communicated the use of BINAP or Tol-BINAP in the synthesis of 2,2Ј-dimethoxy-1,1Ј-dinaphthalene, and showed that the ligand-to-palladium ratio influences the sense of the enantioselection.…”
Section: Introductionmentioning
confidence: 74%